The relative effectiveness of fiscal and monetary policies in promoting Egypt’s output growth: an empirical investigation using an ARDL approach - Israa A. El Husseiny (Journal of Economic Structures, 2023)
Abstract The relative effectiveness of fiscal and monetary policies in promoting economic growth is not sufficiently examined at the empirical level for developing countries, including Egypt in particular. Hence, this paper is the first attempt to empirically examine the relative effectiveness of fiscal and monetary policies in promoting Egypt’s output growth utilizing a time-series data set over the time-period (1960–2019). The study employs the Autoregressive Distributed Lag (ARDL) Bounds testing approach to cointegration to investigate the long run and short run effects of fiscal and monetary policies on Egypt’s output growth under a modified version of the St. Louis equation model. The study finds that both monetary and fiscal policies have a positive impact on the economic activity in the long run. However, while monetary policy seems to be more effective than fiscal policy in stimulating the growth rate of nominal GDP, fiscal policy tends to have a larger, more predictable and faster impact than monetary policy on the real economic activity. Accordingly, Egypt’s policymakers are advised to follow the Keynesian’s prescription in terms of increasing the reliance on fiscal policy compared to monetary policy to achieve macroeconomic stability in both the short run and long run.